2010
DOI: 10.1161/circheartfailure.109.923300
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Ambulatory Intracardiac Pressures and Future Heart Failure Events

Abstract: Background-Intracardiac pressures in heart failure (HF) have been measured in patients while supine in the hospital but change at home with posture and activity. The optimal level of chronic ambulatory pressure is unknown. This analysis compared chronic intracardiac pressures to later HF events and sought a threshold above which higher pressures conferred worse outcomes. Methods and Results-Median pressures were measured every 24 hours from continuous 8-minute segments for 6 months after implantation of hemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(75 citation statements)
references
References 18 publications
6
69
0
Order By: Relevance
“…16 Data from trials of implantable hemodynamic monitors confirm that the risk for heart failure events is tightly coupled to the degree of chronic filling pressure elevation, with progressively higher risk once the median 24-hour pulmonary artery diastolic pressure rises Ͼ18 mm Hg. 17 Chun et al 7 have elegantly outlined a 3-phase terrain of lifetime risk for readmission based on analysis of a cohort of 8543 newly discharged Canadian patients with heart failure (see Figure 1). 18 In this community-dwelling population, 30% of all cardiovascular readmissions occurred within the first 2 months of hospital discharge, and 50% occurred within the 2 months before death, with much lower admission rates (15%-20%) observed in the intercurrent plateau phase.…”
Section: The Landscape Of Readmission: a 3-phase Topographymentioning
confidence: 99%
“…16 Data from trials of implantable hemodynamic monitors confirm that the risk for heart failure events is tightly coupled to the degree of chronic filling pressure elevation, with progressively higher risk once the median 24-hour pulmonary artery diastolic pressure rises Ͼ18 mm Hg. 17 Chun et al 7 have elegantly outlined a 3-phase terrain of lifetime risk for readmission based on analysis of a cohort of 8543 newly discharged Canadian patients with heart failure (see Figure 1). 18 In this community-dwelling population, 30% of all cardiovascular readmissions occurred within the first 2 months of hospital discharge, and 50% occurred within the 2 months before death, with much lower admission rates (15%-20%) observed in the intercurrent plateau phase.…”
Section: The Landscape Of Readmission: a 3-phase Topographymentioning
confidence: 99%
“…[25] This finding is supported by studies showing changes in heart rate variability occurring weeks prior to presentation for AHF, a time during which cardiac filling pressures begin to rise, in the absence of a change in weight, and prior to the development of symptoms. [26] Thus, while symptoms drive most patients with HF to seek treatment, there is at least a moderate degree of discordance between symptoms, cardiac filling pressures, and intravascular volume.…”
Section: Intravascular Volume and Its Role In Acute Heart Failurementioning
confidence: 99%
“…Hemodynamic worsening is characteristic of acute HF; however, few studies have described the changes over time and the short-and longterm implications of hemodynamics in acute HF. In ambulatory patients, dynamic changes in PAP predict acute HF events, 108 and elevations in 24-hour filling pressures precede episodes of decompensation in both HFrEF and HFpEF patients. 109 Aronson et al 38 reported that before treatment, among 242 patients, only 2 (0.83%) had normal PAP (defined as RHC mPAP ≤25 mm Hg); 59.1% had passive PH (mPAP >25 mm Hg, PCWP >15 mm Hg, and PVR ≤3 WU); and 40.1% had reactive PH (mPAP >25 mm Hg, PCWP >15 mm Hg, and PVR >3 WU).…”
Section: Ph In Acute Hfmentioning
confidence: 99%